The effect of location on the incidence of brown rot blossom and shoot blight infection on apricot - Drén, Gábor; Szabó, Zoltán; Nagy, János; Dani, Mária; Thurzó, Sándor; Racskó, József; Tornyai, Julianna; Erdős, Zoltán; Molnár, Barnabásné; Nyéki, József; Holb, Imre (Acta Agraria Debreceniensis, 2005)
The aim of our study was to assess the incidence of brown rot blossom and shoot blight and caused by Monilinia laxa. Assessments of incidence were made on cv. Bergeron (susceptible to brown rot) in a flatland and a hilly growing area (at Cegléd and Gönc, respectively). In 2004, when spring and summer weather conditions were wet and cold, incidence reached 95 % for blossom blight and 33 % for shoot blight in the untreated plots. Blossom blight incidence was 1.5-2 times higher in the flatland area compared to the hilly growing area. During the blooming period of apricot, two (at flower bud stage and at full bloom) and three (at flower bud stage, at full bloom and at petal fall) fungicide applications were necessary for the successful control at Gönc and Cegléd, respectively. The difference between the two orchards was due to the fact that blooming started one week later in the hilly region (at Gönc) than in the flatland region (at Cegléd), therefore, the critical weather period coincided with blooming in the orchard in the hilly region only partially.